Altering chromatin methylation patterns and the transcriptional network involved in regulation of hematopoietic stem cell fate. Issue 10 (13th February 2020) - Shokouhian, Mohammad; Bagheri, Marziye; Poopak, Behzad; Chegeni, Rouzbeh; Davari, Nader; Saki, Najmaldin
Abstract: Hematopoietic stem cells (HSCs) are quiescent cells with self‐renewal capacity and potential multilineage development. Various molecular regulatory mechanisms such as epigenetic modifications and transcription factor (TF) networks play crucial roles in establishing a balance between self‐renewal and differentiation of HSCs. Histone/DNA methylations are important epigenetic modifications involved in transcriptional regulation of specific lineage HSCs via controlling chromatin structure and accessibility of DNA. Also, TFs contribute to either facilitation or inhibition of gene expression through binding to enhancer or promoter regions of DNA. As a result, epigenetic factors and TFs regulate the activation or repression of HSCs genes, playing a central role in normal hematopoiesis. Given the importance of histone/DNA methylation and TFs in gene expression regulation, their aberrations, including changes in HSCs‐related methylation of histone/DNA and TFs (e.g., CCAAT‐enhancer‐binding protein α, phosphatase and tensin homolog deleted on the chromosome 10, Runt‐related transcription factor 1, signal transducers and activators of transcription, and RAS family proteins) could disrupt HSCs fate. Herewith, we summarize how dysregulations in the expression of genes related to self‐renewal, proliferation, and differentiation of HSCs caused by changes in epigenetic modifications and transcriptional networks lead to clonal expansion and leukemic transformation. Abstract : Normal hematopoiesis is controlled by gene expression patterns that guard the balance between self‐renewal and differentiation of hematopoietic stem cells; so that several epigenetic modifiers (e.g., histone/DNA methylation) and transcription factors are involved in the regulation of gene expression and fate in these cells by activation or repression of specific genes. Hence, changes in epigenetic modifications and transcriptional networks lead to clonal expansion and leukemic transformation. RESEARCH HIGHLIGHTS: Chromatin methylation and transcriptional network are involved in the regulation of the balance between self‐renewal and differentiation of hematopoietic stem cells (HSCs). There is a link between aberrant chromatin methylation and transcriptional factors related to the maintenance of HSCs and dysregulation of gene expression. Dysregulation of HSCs gene expression could be related to leukemic transformation.